1976
DOI: 10.1128/aem.31.6.969-976.1976
|View full text |Cite
|
Sign up to set email alerts
|

Liberation of sulfate from sulfate esters by soils

Abstract: When incubated with acid, alkaline, and neutral soils, a variety of synthetic sulfate esters representing the various classes of these compounds was hydrolyzed by enzymes, probably of microbial origin. The appearance of sulfate in the soil water occurred immediately after introduction into the soils with some esters, whereas with others it occurred only after lag periods. Heat treatment destroyed the hydrolytic activity in the soils. The ester sulfate groups-present in humic acid extracted from the soil appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Thus, using a variety of mild extractants (176) unlikely to degrade humic acid, Freney et al (88) found that more HI-reducible S was associated with this latter soil colloid than with fulvic acid. This result is consistent with those of Lowe (159) and Houghton and Rose (113) who found that HI-reducible S represented 39 and 51% of the total S present in humic acid isolated from Alberta and Welsh soils, respectively. In the latter study (113), the presence of sulfate ester groups in the humic acid fraction was confirmed by extraction with methanolic hydrogen chloride and by release of S042after hydrolysis in 6 N HCl at 1000C.…”
Section: Status Of Sulfur In Aerobic Soilssupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, using a variety of mild extractants (176) unlikely to degrade humic acid, Freney et al (88) found that more HI-reducible S was associated with this latter soil colloid than with fulvic acid. This result is consistent with those of Lowe (159) and Houghton and Rose (113) who found that HI-reducible S represented 39 and 51% of the total S present in humic acid isolated from Alberta and Welsh soils, respectively. In the latter study (113), the presence of sulfate ester groups in the humic acid fraction was confirmed by extraction with methanolic hydrogen chloride and by release of S042after hydrolysis in 6 N HCl at 1000C.…”
Section: Status Of Sulfur In Aerobic Soilssupporting
confidence: 92%
“…This result is consistent with those of Lowe (159) and Houghton and Rose (113) who found that HI-reducible S represented 39 and 51% of the total S present in humic acid isolated from Alberta and Welsh soils, respectively. In the latter study (113), the presence of sulfate ester groups in the humic acid fraction was confirmed by extraction with methanolic hydrogen chloride and by release of S042after hydrolysis in 6 N HCl at 1000C. The collective results of these studies (88,159,176) and others (90,91,158) suggest that no one procedure is entirely suitable for assessing the heterogeneity of compounds comprising the HIreducible S fraction of soil.…”
Section: Status Of Sulfur In Aerobic Soilssupporting
confidence: 92%
See 3 more Smart Citations